Capacity Building of Micro, Small, and Medium Enterprises Through Digital Marketing Training in Gamping and Tegaren Village, Trenggalek Regency - Rahayudi, MT (Scopus ID : 37079427500 (TRI DHARMA MANDIRI: Dissemination and Downstreaming of Research to the Community (Journal of Community Engagement), 2025)
Digital transformation in rural areas drives micro, small, and medium enterprises (MSMEs) to adopt technology-focused marketing. This project enhances MSMEs’ digital marketing expertise in Gamping and Tegaren Villages, Trenggalek Regency, through focused, structured training. The methodology implements a training cycle: needs assessment, strategic planning, content development, delivery, and evaluation. The training covers digital marketing principles, affiliate marketing, and content marketing. Participants gained more substantial knowledge and hands-on skills in utilizing digital platforms for promotion, crafting persuasive content, and launching online business accounts. The evaluation revealed increased digital engagement, high participant motivation, and the formation of a collaborative digital marketing learning group. This project advances digital empowerment among rural MSMEs and exemplifies the innovative economy model in local development. These findings reinforce the need for flexible, context-specific training to support continuous digital transformation.